Global Insights into Idiom Teaching for English Language Learners: A 20-Year Bibliometric Review - Tauhid, Aura Bunga; Rohmah, Zuliati (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Idioms are a challenging yet essential subject in language learning, especially for English as a Foreign Language (EFL) learners. Although many studies have explored idiom teaching strategies, there has been little bibliometric analysis to track global research trends in this area. This study fills this gap by conducting a 20-year bibliometric analysis to gain a comprehensive view of the study of idioms in EFL teaching. The current study aims to analyze the number of publications produced, authors who have contributed, the number of countries producing articles, keyword trends to highlight emerging areas of interest, the most cited documents, and the most cited countries in articles on idiom teaching and learning. The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method was applied to analyze 131 articles published between 2004 and 2024 in the Scopus database using VOSviewer and Biblioshiny-R software, focusing on idioms in English language teaching and learning. The findings show a trend of article publications indicating an increasing awareness of this topic. Ahmadi A. is the author who produced the largest number of publications where significant contributions were found from countries such as Iran and China. The keywords that often appear include “idiom”, “culture”, and “translation” which highlight the importance of culture and translation in the discussion of idioms. In addition, the most cited article can be seen from Hayati's article and the most cited country is Iran. This study concludes that future research should further explore the integration of idiomatic expressions into language learning curricula.